2012
DOI: 10.1167/iovs.11-8572
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography ofβ-zone Peripapillary Atrophy: Influence of Myopiaand Glaucoma

Abstract: PPA bed configurations detected by SD-OCT were classified into three types. The lack of BM on the PPA bed was closely associated with myopia. The downward-curved appearance of BM may be related to the anatomic changes associated with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…Our histological results on a parapapillary region (''gamma'' zone) between the border of the optic nerve (as defined by the outer surface of the pia mater) and the beginning of Bruch's membrane confirms previous clinical studies and histologic single case descriptions [7][8][9][10][11][12][13][14][15]. Using spectral-domain optical coherence tomography, Hayashi and colleagues examined the peripapillary atrophy in 100 patients with primary open-angle glaucoma and in 100 normal subjects [13].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our histological results on a parapapillary region (''gamma'' zone) between the border of the optic nerve (as defined by the outer surface of the pia mater) and the beginning of Bruch's membrane confirms previous clinical studies and histologic single case descriptions [7][8][9][10][11][12][13][14][15]. Using spectral-domain optical coherence tomography, Hayashi and colleagues examined the peripapillary atrophy in 100 patients with primary open-angle glaucoma and in 100 normal subjects [13].…”
Section: Discussionsupporting
confidence: 82%
“…This finding was corroborated by clinical studies [6]. For medium myopic eyes, recent clinical investigations using optical coherence tomography have shown another feature: between a beta zone (characterized by Bruch's membrane) and the border of the optic disc, the images demonstrated a zone which was composed simply of sclera and overlying retinal nerve fiber layer tissue [7][8][9][10][11][12][13][14]. We therefore, reassessed histological slides of human globes without and with axial elongation and without and with glaucoma.…”
Section: Introductionsupporting
confidence: 70%
“…4,8,10 Recent histologic 11 and spectraldomain optical coherence tomography (OCT) [12][13][14][15][16] imaging studies proposed a new classification for beta-PPA, dividing it into two subsets that are indistinguishable by clinical examination: an area with intact Bruch's membrane, still termed beta-PPA, and an area lacking Bruch's membrane, termed gamma-PPA. Recent studies showed that gamma-PPA had a higher association with myopia, [11][12][13]15 and could represent anatomical changes resulting from globe elongation, whereas beta-PPA with intact Bruch's membrane has a higher association with glaucoma, 11,14,15,17 reduced choroidal volume, 17 and older age, 13,16,17 possibly representing degenerative changes. Therefore, this new subclassification of beta-PPA according to OCT findings could potentially be used to differentiate myopic eyes with and without glaucoma.…”
mentioning
confidence: 99%
“…3,4 The higher susceptibility to glaucoma is hypothesized at a given IOP in myopic eyes from the conformational changes according to axial length (AL) elongation. 5 A variety of morphologic changes in highly myopic eyes have been documented using histology and optical coherence tomography (OCT), for example, flattening and enlargement of the optic disc, 6 lamina cribrosa or scleral thinning, 7 peripapillary atrophy (PPA) enlargement, 8 scleral deformation between the optic nerve head (ONH) and the macula, 9 and scleral pit formation inside the ONH or PPA, 10 some of which are believed to be partly responsible for increased susceptibility to glaucoma. However, the geometric analysis around the ONH in highly myopic eyes has not been well investigated.…”
mentioning
confidence: 99%